Geoecological basis of nature protection and holistic use of natural resources in the Fergana valley - Khamidov Abdusamad; Bakhtiyorova Dilfuza; Saydullayeva Surayyo; Janizoqova Gulshoda; Yusupova Kamola (E3S Web of Conferences)
The article describes the period in the Fergana Valley and adjacent regions in the 1970s and early 1980s, when environmental issues and the deterioration of environmental condition were just beginning to be placed the agenda. Firstly, scientific conditions on the geographical sides of the holistic use of existed hydro resources, natural complex changes with the influence of anthropogenic factors in the effects of watering areas on the natural world was analyzed. In the late 1980s, researchers looked into and carried out a thorough analysis of the regional and regional ecological condition and natural issues that appeared in the Fergana Valley. These evaluations were the first comprehensive scientific analysis in environmental protection in the region. Many sensitive concerns were brought up at that time. In the highland regions of the Fergana Valley, various natural and natural-anthropogenic systems were formed: deserts, hills. It is an ancient irrigated oasis, a fast-growing and densely populated industrial-agrarian region with developed industry, farming, transport and other industries. It is emphasized that the growth and practical implementation in geoecological foundations of conservation and sensible application of natural resources in the Fergana Valley are relevant.